Martu Storytellers: Aboriginal Narratives Within the Academy - Somerville, Craig; Somerville, Kirra; Wyld, Frances (The Australian Journal of Indigenous Education, 2010)
Abstract The Martu people originate from the Pilbara region in Western Australia. Despite policies of removal, incarceration in prison and the need to leave community fo health services, Martu maintain identity and connection to country. Their narratives have used to inform a wider Australian audience about the history and culture of Aboriginal people. But the stories have also received criticism and been the subject of a Westernised anthropological view. With the emergence of storytelling as method in the academy, a new space is being created for Aboriginal and non-Aboriginal people to find a more robust foothold within the Social Sciences to story our world. This paper is written by three Martu people who position storytelling as transmission and preservation of cultural knowledge and to privilege a voice to speak back to Western academics. Storytelling also brings an opportunity to engage with an Aboriginal worldview, to use narrative as an inquiry into ontology and one's connection to people and place. This brings benefits to all Australians seeking stories of country, connection and identity.